The inevitable deservingness gap: A study into the insurmountable immigrant penalty in perceived welfare deservingness. (May 2019) - Reeskens, Tim; van der Meer, Tom
As the asylum crisis hit Europe in tandem with the Great Recession, concerns about declining support for equal welfare provision to immigrants grow. Although studies on welfare deservingness show that immigrants are deemed least entitled to welfare compared to other target groups, they have fallen short of isolating welfare claimants' identity (i.e. foreign origin) with competing deservingness criteria that might explain the immigrant deservingness gap. This article studies the importance of welfare claimants' foreign origins relative to other theoretically relevant deservingness criteria via a unique vignette experiment among 23, 000 Dutch respondents about their preferred levels of unemployment benefits. We show that foreign origin is among the three most important conditions for reduced solidarity, after labour market reintegration behaviour (reciprocity) and culpability for unemployment (control). Furthermore, favourable criteria do not close the gap between immigrants and natives in perceived deservingness, emphasizing the difficulty of overcoming the immigrant penalty in perceived welfare deservingness. We conclude our findings in the light of ongoing theoretical and political debates.